If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 7 + 10 = 11x Reorder the terms: 7 + 10 + 2x = 11x Combine like terms: 7 + 10 = 17 17 + 2x = 11x Solving 17 + 2x = 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 17 + 2x + -11x = 11x + -11x Combine like terms: 2x + -11x = -9x 17 + -9x = 11x + -11x Combine like terms: 11x + -11x = 0 17 + -9x = 0 Add '-17' to each side of the equation. 17 + -17 + -9x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + -9x = 0 + -17 -9x = 0 + -17 Combine like terms: 0 + -17 = -17 -9x = -17 Divide each side by '-9'. x = 1.888888889 Simplifying x = 1.888888889
| 1.7(r+1)=6.8 | | 9-4(2x-1)=45-4x | | (-3-7)+(4+7)= | | -152=4(-8+5m) | | b/9=a | | b/9=8 | | 38n+1=25 | | 3=-4/w-7 | | 3(-5a+9)-2(4a+6)= | | 5.25(2)+3.25=10.25+1.75(2) | | 6x^3-12x^2+10x-20=0 | | -10w+2=2w+18 | | 13x+11=12x+3 | | 2(4x+7)+6x=5(x+10) | | -20+n=3.50 | | (6d+5)-(23d)= | | 5/4-1/3x1/2 | | 11=2x-11 | | -34+2x-7x=76 | | -5x+12=-12x+-12 | | 9-1/3a=-4 | | .25n=-12 | | 2x-9+x+3=-27 | | 4x-3=2(X+13) | | 2x-9+n+3=-27 | | -5x+12=-5x+-12 | | 16Y-7y=500 | | 4x-3+0=-3x-4 | | ((12k^2h)-(3kh^2))/3kh | | 0.25(8-4p)+2p=12 | | 2x+19y=300 | | 60=x+71 |